2019
DOI: 10.1002/pssa.201800947
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Activity of ZnO Toward the Degradation of Methylene Blue Dye: Effects of Fe3+ and Sn4+ Doping

Abstract: ZnO, Fe 0.01 ZnO, Sn 0.05 ZnO, and Fe 0.01 Sn 0.01 ZnO photocatalysts are prepared by a simple low-temperature solution method using Zn(NO 3 ) 2 , Fe(NO 3 ) 3 , SnCl 4 , and NaOH as raw materials. X-ray diffraction, field-emission scanning electron microscopy, high-resolution transmission electron microscopy, energy-dispersive X-ray spectroscopy, Brunauer-Emmett-Teller surface area analysis, X-ray photoelectron spectroscopy, ultraviolet-visible diffusion spectroscopy, and photoluminescence spectroscopy are per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…8 , edge, valence band (VB), conduction band (CB) and the edge potential of Chitosan and ZnO semiconductor were measured by applying the following equations: where E CB represent the conduction band edge potential, E VB stand for the valence band edge potential, X is the electronegativity of the semiconductor, E g shows the bandgap of the semiconductor and E e stands for the energy of free electrons on the hydrogen scale which is about 4.5 eV vs. NHE 50 . The electronegativity of ZnO had been reported 5.47 eV 51 . The E VB and E CB of ZnO were measured to be 2.615 eV and − 0.135 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…8 , edge, valence band (VB), conduction band (CB) and the edge potential of Chitosan and ZnO semiconductor were measured by applying the following equations: where E CB represent the conduction band edge potential, E VB stand for the valence band edge potential, X is the electronegativity of the semiconductor, E g shows the bandgap of the semiconductor and E e stands for the energy of free electrons on the hydrogen scale which is about 4.5 eV vs. NHE 50 . The electronegativity of ZnO had been reported 5.47 eV 51 . The E VB and E CB of ZnO were measured to be 2.615 eV and − 0.135 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of dopants significantly changes the band gap of ZnO as a result of the appearance of intermediate energy levels within the forbidden region [17]. Additionally, this process can affect the crystalline structure, surface area, crystallite size and morphology of this oxide, as well as its physical and chemical properties [18][19][20][21][22][23]. In order to increase its technological applications, such characteristics can be tuned by choosing appropriate dopants and their concentration [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the incorporation of metallic ions such as Co 2+ [27,28], Ni 2+ [29,30], Fe 3+ [30] and Sn 4+ [20], into the ZnO structure to tune its properties, including its photocatalytic visible-light response, has also been investigated. Ji et al [20] showed that the degradation rate of methylene blue by Sn 0.05 ZnO reached 99.61% after 120 min of illumination, which was approximately 2.2 times higher than undoped ZnO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E CB = E VB -E g (5) Where E CB represent the conduction band edge potential, E VB stand for the valence band edge potential, X is the electronegativity of the semiconductor, E g shows the bandgap of the semiconductor and E e stands for the energy of free electrons on the hydrogen scale which is about 4.5 eV vs. NHE 38 . The electronegativity of ZnO had been reported 5.47 eV 39 . The E VB and E CB of ZnO were measured to be 2.615 eV and − 0.135 eV, respectively.…”
Section: Photocatalytic Mechanismmentioning
confidence: 99%